RENCANA BISNIS PENGEMBANGAN USAHA PENGOLAHAN KOPI ARABIKA (Coffea arabica) DI SUBAK ABIAN ULIAN MURNI, KINTAMANI – BANGLI - Pemaron S, Ida Bagus Gede Ardyana; Satriawan, I Ketut; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
Subak Abian Ulian Murni is a business unit of procesing and marketing of Arabica coffee at Kintamani, Bangli. It has a plans to develop its bussines. The research conducted to formulate business development strategy and determine the feasibility of developing a business plan Arabica coffee processing in Subak Abian Ulian Murni. This research used SWOT analysis to formulate strategies and analysis of market and marketing aspects, technical and technological aspects, management and human resources aspects, and financial aspects with the eligibility criteria such as NPV, IRR, B/C Ratio, PBP, and BEP to evaluate the feasibility of business. SWOT analysis in Subak Abian Ulian Murni based of matrix position was in quadrant I, which means Subak Abian Ulian Murni had the internal strength that can take to advantage of existing opportunities aggressively. The resulting strategy was Arabica coffee powder products introduced to the market with aggressive promotion and produce premium quality of Arabica coffee powder to support Kintamani as a tourist destination. Results of feasibility study analysis of financial aspects was feasible seen NPV Rp. 735.093.613, IRR are 40,7%, B/C Ratio are 1,074, PBP 2 years 8,4 month, and BEP while sales of 2.349,75 kg with supported by market and marketing aspects, technical and technological aspects, and aspects of management and human resources.
Keywords: 58